Penerapan 4S dan 1R (Senyum, Salam, Sapa, Salim dan Rapih) dalam Peningkatan Kinerja Perawat - Aris Fitriyani; Maisje Marlyn Kuhu; Munjiati Munjiati (Prodi Keperawatan Purwokerto, 2019)
Nurses need to implement 4S and 1R (Smile, Greeting, Sapa, Salim, and Natty), which will support the implementation of the tasks of nurses in providing nursing care to patients. Implementation 4S and 1R allows the nurse was not emotional in dealing with patients who are good variety of attitudes, behaviors, socioeconomic status and so on. Implementation 4S and 1R nurses make positive personality that can improve the performance of nurses.To determine the effect of the application of 4S and 1 R on the performance of nurses in Hospital Family Dadi Purwokerto.This type of research is pre experimental research design pre-post test one group. The study population was a nurse at the Hospital Purwokerto Family Dadi much as 39 nurses. Samples were taken with total sampling of nurses hospitalization in Purwokerto RSDK with kriteria inclusion: nurse graduate Nursing DIII, and length of employment 3 years amounted to 35 nurses. The intervention will involve the implementation of a shared commitment 4S and 1 R for 1 week working in the inpatient unit RSDK Purwokerto. Data analysis techniques used in this study is a statistical test Pairs T-test.Nurses majority 24 years old, Muslim, unmarried, has a female gender, education background and has a long working DIII 1 year. There is a significant influence on the performance of nurses before and after being given the shared commitment and implementation 4S 1R and there are significant differences in the performance of nurses between before and after being given the shared commitment and 1R 4S application on nurse-patient RSDK Purwokerto with p = 0.000.